2017
DOI: 10.1016/s2215-0366(17)30253-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for HIV, hepatitis B, and hepatitis C in people with severe mental illness: a total population study of Sweden

Abstract: SummaryBackgroundSevere mental illness is associated with increased morbidity and mortality. The elevated risk of blood-borne viruses (BBVs) in people with severe mental illness is of concern, but the full extent of this problem is unclear. We aimed to determine the prevalence of and risk factors for BBVs in people with severe mental illness.MethodsIn this nationwide, population-based, cross-sectional study, we estimated the point prevalence of HIV, hepatitis B (HBV), and hepatitis C (HCV) in people with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…Previous studies also reported that HIV/HBV/HCV co-infected patients have a higher mortality rate than each of the HIV/HCV and HIV/HBV co-infected patients. 52,53 We were not able to show this but we only had a small sample size of triple co-infection patients in our study. Currently, there are no recommendations for treating triple co-infection patients in the latest Chinese treatment guidelines.…”
Section: Association Between Hepatotoxicity and Hepatitis Co-infectmentioning
confidence: 83%
“…Previous studies also reported that HIV/HBV/HCV co-infected patients have a higher mortality rate than each of the HIV/HCV and HIV/HBV co-infected patients. 52,53 We were not able to show this but we only had a small sample size of triple co-infection patients in our study. Currently, there are no recommendations for treating triple co-infection patients in the latest Chinese treatment guidelines.…”
Section: Association Between Hepatotoxicity and Hepatitis Co-infectmentioning
confidence: 83%
“…In a national Swedish survey, the patient safety culture was rated lower than in somatic care [32]. The lack of documentation of physical status during psychiatric hospital care is troublesome, as patients with a serious mental illness have higher rates of physical conditions, such as obesity, diabetes, hypertension and HIV/AIDS [33,34], and risk behaviour, such as smoking, drinking alcohol and physical inactivity [35].…”
Section: Discussionmentioning
confidence: 99%
“…We defined diagnoses of BPD, schizophrenia, and NAP in line with previous research using Swedish National Patient Registers. 12 , 13 Individuals had at least 1 record of inpatient or outpatient contact with codes from the International Classification of Diseases, Ninth Revision ( ICD-9 ) and International Statistical Classification of Diseases and Related Health Problems, Tenth Revision ( ICD-10 ) consistent with the diagnosis (eTable 1 in the Supplement ) and a period of drug treatment with an appropriate psychotropic medication (antipsychotic, lithium, or anticonvulsant class mood stabilizer) from October 1, 2005, through December 31, 2016. Validation studies suggest that using inpatient SMI diagnosis alone has high positive predictive power (0.94) but potentially misses suitable patients owing to type II error (negative predictive power, 0.23).…”
Section: Methodsmentioning
confidence: 99%